EMPOWERING LANGUAGE LEARNING: THE CRITICAL ROLE OF MODERATORS IN DUOLINGO’S GERMAN DISCUSSION BOARDS - Neuschafer, Tom (LLT Journal: A Journal on Language and Language Teaching, 2024)
Asynchronous discussion boards provide learners with an online platform to collaborate and communicate. This study aims to investigate the pivotal role of moderators in managing and enhancing the dynamics of asynchronous discussion boards in Duolingo’s German language learning environment. There are nearly nine million individuals who use Duolingo to learn German. This study implemented netnography to examine six moderators on Duolingo German language discussion boards. From an initial potential pool of 12 participants, two participants were chosen at random from three levels of engagement: high, moderate, and lower, for a total of six moderators. Moderators who commented at least 150 times were considered highly engaged; those with at least 25 comments were moderately engaged, and those with fewer than 25 comments were lower engaged. Data collection involved analyzing comments posted between 2013 and 2022. The study examined the frequency of comments, number of language badges, German course level, total posts, and years using Duolingo. However, activities occurring ‘behind the scenes,’ such as deleting inappropriate comments and providing feedback to developers, were not analyzed. The analysis covered 26 discussion boards, with five boards per participant, except for one user. Thematic analysis was used to identify patterns in moderator behavior and its impact on learner engagement. This methodology supported the investigation of how Duolingo German moderators oversee asynchronous discussion boards, allowing us to analyze and understand the evolving needs and engagement levels of learners within this online community. The results of the netnography showed that there were three themes. The findings support past research, which suggests the moderator role extends beyond mere oversight, providing management of online discussion boards, contributing significantly to the success of language learning programs, and enhancing the overall learning experience.